2013
DOI: 10.1002/oby.20326
|View full text |Cite
|
Sign up to set email alerts
|

A metabolically healthy obese phenotype in hispanic participants in the IRAS family study

Abstract: Objective Some obese individuals appear to be protected from developing type 2 diabetes mellitus and cardiovascular disease (CVD). This has led to characterizing body size phenotypes based on cardiometabolic risk factors specifically as obese or overweight, and as metabolically healthy (MH) or metabolically abnormal (MA) based upon blood pressure, lipids, glucose homeostasis and inflammatory parameters. The aim of this study was to measure the prevalence of and describe fat distribution across these phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
2
8
1
Order By: Relevance
“…This is in contradiction with lower liver enzymes levels associated with metabolic health defined as no insulin resistance in post menopausal obese Caucasian women (Messier et al, 2010) and associated with MHO phenotype in Korean people with overweight or obesity (Hong et al, 2013). However, in our population, the prevalence of increased γ glutamyltransferase in MUO was slightly higher than in definite MHO individuals, and was probably associated with hepatic steatosis (Samaropoulos et al, 2013;Stefan et al, 2008). In addition, an increasing number of features of the metabolic syndrome was associated with fatty liver index, an estimate of liver fat content (Bedogni et al, 2006;Messier et al, 2010), suggesting an association between non alcoholic fatty liver disease and unfavourable metabolic and cardiovascular (Oni et al, 2013) profile.…”
Section: Patients' Characteristicscontrasting
confidence: 83%
“…This is in contradiction with lower liver enzymes levels associated with metabolic health defined as no insulin resistance in post menopausal obese Caucasian women (Messier et al, 2010) and associated with MHO phenotype in Korean people with overweight or obesity (Hong et al, 2013). However, in our population, the prevalence of increased γ glutamyltransferase in MUO was slightly higher than in definite MHO individuals, and was probably associated with hepatic steatosis (Samaropoulos et al, 2013;Stefan et al, 2008). In addition, an increasing number of features of the metabolic syndrome was associated with fatty liver index, an estimate of liver fat content (Bedogni et al, 2006;Messier et al, 2010), suggesting an association between non alcoholic fatty liver disease and unfavourable metabolic and cardiovascular (Oni et al, 2013) profile.…”
Section: Patients' Characteristicscontrasting
confidence: 83%
“…However, we did not have available data on waist circumference or fat distribution in this study, and it was suggested that the inflammatory status might play an important role in defining metabolic health. Also, studies of other populations that investigated characteristics of metabolic phenotypes reported that differences in fat distribution were observed across obese phenotypes . Nonetheless, our results indicated that the risk of diabetes could substantially vary if we considered changes in and stability of MH‐O and MA‐O phenotypes that were defined using common clinical markers in this study.…”
Section: Discussionmentioning
confidence: 75%
“…Some authors have found higher adiponectin concentrations in MHO as compared with MAO, which has been related to reduced inflammation and improved metabolic function (25,26). The similarly reduced levels observed in the current study have been reported previously (7,27,28) and together with the comparable concentrations of leptin and resistin suggest that MHO and MAO show a very similarly altered adipokine profile.…”
Section: Discussionmentioning
confidence: 99%